2021
DOI: 10.11113/jurnalteknologi.v83.14706
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Spray Dried Coamorphous Solids to Improve the Solubility and Dissolution Rate of Atorvastatin Calcium

Abstract: Atorvastatin calcium (AC) is a statin drug used to lower cholesterol. Its crystalline form is usually found in the market with low solubility properties. The amorphization of crystalline AC is a technique used to increase its solubility however; the amorphous form has less thermodynamic stability. Therefore, to increase the solubility properties of its crystalline form, an AC coamorphous solid was prepared. This coamorphous solid was prepared using spray drying techniques, and coformers such as isonicotinamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Dipicolinic acid has a broad absorption peak at wave number 3254-2363 cm -1 (O-H stretching) and a sharp absorption peak at 1692 cm -1 (C=O stretching). The FTIR spectra of both materials showed the same specific absorption peaks as mentioned in the literature (Wicaksono et al, 2021;Hiendrawan et al, 2016). The FTIR spectra of atorvastatin calcium -dipicolinic acid multicomponent solids showed a change in the intensity and shift of the absorption peak in the functional groups of atorvastatin calcium and dipicolinic acid.…”
Section: Dsc Thermogramsupporting
confidence: 75%
See 3 more Smart Citations
“…Dipicolinic acid has a broad absorption peak at wave number 3254-2363 cm -1 (O-H stretching) and a sharp absorption peak at 1692 cm -1 (C=O stretching). The FTIR spectra of both materials showed the same specific absorption peaks as mentioned in the literature (Wicaksono et al, 2021;Hiendrawan et al, 2016). The FTIR spectra of atorvastatin calcium -dipicolinic acid multicomponent solids showed a change in the intensity and shift of the absorption peak in the functional groups of atorvastatin calcium and dipicolinic acid.…”
Section: Dsc Thermogramsupporting
confidence: 75%
“…Previous studies have shown that the formation of multicomponent solids of atorvastatin calcium, carried out with maleic acid coformers using the spray drying method, can increase the solubility of atorvastatin calcium in water significantly when compared to its pure solids form (Wicaksono et al, 2021). However, in evaluating lipid-lowering activity, the atorvastatin calcium-maleic acid multicomponent solids did not show increased lipid-lowering activity when compared to the lipid-lowering activity of pure atorvastatin calcium (Wicaksono et al, 2022).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, PMCA is an active ingredient that is very difficult to dissolve with a solubility of 0.71 mg/mL at 25°C [1], [2]. Low solubility is a major problem in the development of new drugs because it affects the rate of drug dissolution and limited the drug's absorption [3], [4]. Therefore, it urges to find a method to increase the solubility of PMCA.…”
Section: Introductionmentioning
confidence: 99%